Phylogenetics, biogeography, and life history evolution in the broadly distributed treefrog genus Dendropsophus (Anura: Hylidae: Hylinae) - Whitcher, Courtney; Orrico, Victor G.D.; Ron, Santiago; Lyra, Mariana L. [UNESP]; Cassini, Carla S.; Ferreira, Rodrigo B.; Nakamura, Daniel Y.M.; Peloso, Pedro L.V.; Rada, Marco A.; Rivera-Correa, Mauricio; Sturaro, Marcelo J.; Valdujo, Paula H.; et al. (Elsevier, 2025)
Dendropsophus is one of the most species-rich genera of hylid treefrogs. Recent studies integrating Sanger-generated mitochondrial and nuclear loci with phenomic characters (SP) have advanced understanding of this clade, but questions about its internal relationships and biogeographic history persist. To address these questions, we used anchored hybrid enrichment (AHE) to combine 432 nuclear loci for 78 taxa (72 % of species) with published data. Quantitatively, the impact of the AHE data was modest, with compositional differences in only three recognized clades and more than 80 % of the clades in the AHE + SP analyses also supported in the SP-only analyses. Nevertheless, the impact of AHE was crucial for resolving and increasing support for multiple nodes. We transferred one species of the former D. ruschii group to the D. decipiens group and redefined the D. leucophyllatus group to avoid paraphyly. We estimated divergence times to reconstruct the clade's biogeographic history. We also examined evolution of oviposition sites and assessed its effect on lineage accumulation. Dendropsophus likely originated ∼ 57 mya, predating the Andean uplift, with some taxa showing dispersal patterns less constrained by ecological changes than previously thought.
Keywords: Amphibian; Biogeography; Comparative methods; Neotropical; Phylogenetics